ELECTROCHEMICAL RESPONSE OF 70Co–30Ni HIGHLY BRANCHED 3D-DENDRITIC STRUCTURES FOR CHARGE STORAGE ELECTRODES. (10th June 2015) - Silva, R.P.; Eugénio, S.; Duarte, R.; Silva, T.M.; Carmezim, M.J.; Montemor, M.F.
Highlights: Electrodeposition of a 70Co–30Ni alloy with 3D dendritic morphology. Formation of redox active hydroxide and oxy-hydroxide nanoplates. Capacity retention above 70% in a 8000 cycle test. ABSTRACT: A 70Co–30Ni dendritic alloy was produced on stainless steel by pulse electrodeposition in the cathodic domain, and oxidized by potential cycling. X-ray diffraction (XRD) identified the presence of two phases and scanning electron microscopy (SEM) evidenced an open 3D highly branched dendritic morphology. After potential cycling in 1 M KOH, SEM and X-ray photoelectron spectroscopy (XPS) revealed, respectively, the presence of thin nanoplates, composed of Co and Ni oxi-hydroxides and hydroxides over the original dendritic film. Cyclic voltammetry tests showd the presence of redox peaks assigned to the oxidation and reduction of Ni and Co centres in the surface film. Charge/discharge measurements revealed capacity values of 121 mAh g −1 at 1 mA cm −2 . The capacity retention under 8000 cycles was above 70%, stating the good reversibility of these redox materials and its suitability to be used as charge storage electrodes. Electrochemical impedance spectroscopy (EIS) spectra, taken under different applied bias, showed that the capacitance increased when the electrode was fully oxidized and decreased when the electrode was reduced, reflecting different states-of-charge of the electrode.